Gasification Processes Old and New: A Basic Review of the Major Technologies - Ronald W. Breault (Energies, 2010)
This paper has been put together to provide a single source document that not only reviews the historical development of gasification but also compares the process to combustion. It also provides a short discussion on integrated gasification and combined cycle processes. The major focus of the paper is to describe the twelve major gasifiers being marketed today. Some of these are already fully developed while others are in various stages of development. The hydrodynamics and kinetics of each are reviewed along with the most likely gas composition from each of the technologies when using a variety of fuels under different conditions from air blown to oxygen blown and atmospheric pressure to several atmospheres.